Dynamic DNA binding licenses a repair factor to bypass roadblocks in search of DNA lesions - Maxwell W. Brown (Nature Portfolio, 2016)
DNA-binding proteins need to scan the genome to find their targets though how this occurs in the crowded nuclear environment is poorly understood. Here the authors use single-molecular fluorescence to show the repair complex Msh2-Msh3 can hop over blocks that impede the sliding complex Msh2-Msh6.